Prognostic value of the BAB index and a machine learning model integrating the BAB index for predicting mortality in acute ST-segment elevation - Xu, Haonan; Gu, Tianshu; Zhang, Shuo; Zhao, Shuang; Xie, Juan; Zhao, Jinhua; Tse, Gary; Liu, Tong; Chen, Kangyin; Fu, Huaying (Frontiers in Nutrition, 2026)
BackgroundThe high mortality in ST-segment elevation myocardial infarction (STEMI) is associated not only with organ dysfunction and complications, but also with nutritional status. We aim to develop and validate a simple prognostic tool based on routinely serum biomarkers for predicting short- and long-term mortality in patients with STEMI, and to assess its contributing role in machine learning (ML) models.MethodsObservational multicenter data from the Tianjin Coronary Artery Disease (CAD) Database (2010–2021) were analyzed. The predictive abilities of biomarkers were identified via multivariable Cox regression. The BAB Index was calculated as Log10(NT-proBNP × ALT × BUN). Prognostic performance was evaluated by area under the curve (AUC) and compared with the CAMI-STEMI score. Validation included Cox regression, restricted cubic spline analysis (RCS), Kaplan–Meier survival, and subgroup analyses. ML models incorporating the BAB Index were constructed to verify the contributing roles of the BAB index in predicting 1-month and 1-year mortality.ResultsAmong 8,002 STEMI patients, BAB Index showed strong discriminatory power for 1-month (AUC = 0.804) and 1-year mortality (AUC = 0.794), comparable to the CAMI-STEMI score (P = 0.641). Higher BAB Index were independently associated with increased mortality (P < 0.001). RCS revealed a linear relationship, and Kaplan–Meier analysis confirmed worse survival with higher BAB Index (P < 0.001). Subgroup analyses demonstrated consistent findings. The XGBoost model achieved the highest performance for both 1-month (AUC 0.873) and 1-year mortality (AUC: 0.871), with BAB Index ranked among the top predictive features.ConclusionsBAB Index is a simple, effective tool for predicting short- and long-term mortality in STEMI. BAB index maintains a leading position among interpretable ML models.